Growth pattern of children with congenital heart disease before and after open heart surgery - Jamei Khosroshahi, Ahmad; Shoaran, Maryam; Ghaffari, Shamsi; Shabanpour, Ehsan; Seraj Ebrahimi, Parmida; Ansari, Akram; Khosravi, Reza; Azarm, Eftekhar; Sadeghvand, Shahram; Erabi, Gisou; Chichagi, Fatemeh (Frontiers in Pediatrics, 2025)
BackgroundCongenital heart disease (CHD) affects 0.8%–1.2% of newborns globally, posing challenges to growth and nutrition. This cross-sectional study, conducted at Shahid Madani Hospital, Tabriz, aimed to assess growth patterns in 200 CHD patients (cyanotic and non-cyanotic) aged 1 month to 15 years before and after open-heart surgery.MethodsData were collected from March 2016 to March 2020, including patient records, growth measurements, surgical details, and postoperative outcomes. Patients were categorized into cyanotic and non-cyanotic groups. Inclusion criteria involved CHD patients undergoing surgery with 1–2 years of follow-up. To compare growth disorders between cyanotic and non-cyanotic groups, logistic regression was used, adjusting for age and gender. The significance level was set at 0.05 for statistical analysis.ResultsA total of 200 patients suffered from CHD underwent growth disorder examination in before and after surgery. The prevalence of weight growth disorder reduced from 44% in preoperative to 3.5% in 2 years after surgery. Similarly, the height and head circumference growth disorders experienced reduction from 40.5% and 6.5% to 9.5% and 1.5%, respectively. Generally, growth disorders were higher in cyanotic compared to non-cyanotic group. However, this difference was only significant in weight and height growth disorders in cyanotic vs. non-cyanotic groups after 1 year from surgery (p = 0.024, 0.038). The duration of PICU (8.11 ± 5.47 vs. 8.84 ± 5.83 days) and ward (4.40 ± 3.46 vs. 3.57 ± 2.20 days) hospitalization was longer for non-cyanotic vs. cyanotic groups, both suffering from growth disorders.ConclusionDespite advancements in pediatric cardiac surgery, CHD children face growth challenges, especially in the cyanotic group. Timely surgical intervention demonstrated improvements, but growth disorders persisted in the long term, impacting PICU and inpatient ward stays. Targeted interventions are crucial to mitigate mortality risks associated with growth impairments in CHD children.